NEW ASPECTS OF LABORATORY DIAGNOSTICS OF LIVER FIBROSIS - Nabieva Farangiz,; Avazova Gulzoda,; Baratova Nodira,; Ergashova Shakhlo, (TADQIQOTLAR, 2026)
Abstract.  Currently,  the  mortality  rate  from  terminal  stage  liver  fibrosis  - cirrhosis - ranks 9th in the world among all causes of death and 6th among people of working  age,  amounting  to  14  to  30  cases  per  100  thousand  people.  The  article presents current data on the methods used for the diagnosis of liver fibrosis. To date, liver  biopsy,  the  study  of  direct  and  indirect  serological  markers,  as  well  as instrumental  methods  are  used.  Laboratory  diagnosis  of  fibrosis  at  this  stage  of development of medicine is aimed at the development, improvement and application of non-invasive diagnostic methods. This is due to the ability to track the dynamics of the disease, the lack of contraindications and other advantages.